Social and cultural strategies in the frugal living practices of UNNES students amidst contemporary economic pressures - Niswatun Mufarrikhah; Harto Wicaksono (Universitas Muhammadiyah Malang, 2025)
This study aims to understand the socio-cultural strategies used by students in practicing a frugal lifestyle amidst economic challenges and a consumer culture in higher education. This study was conducted at Semarang State University (UNNES) using a qualitative approach and descriptive design. Data were collected through in-depth interviews, observation, and documentation with six primary informants and eight supporting informants selected purposively. Data analysis used the interactive model of Miles and Huberman, which includes data reduction, data presentation, and conclusion drawing. The research results show that students implement three main strategies, namely (1) rational financial management through budget recording and planning; (2) controlling consumption by limiting daily expenses and prioritizing basic needs; and (3) socio-cultural adaptation through internalizing the values ​​of simplicity, solidarity among boarding housemates, and family habits. These three strategies illustrate that a frugal lifestyle is not only a response to economic limitations, but also an expression of social and cultural values ​​that shape student identity. Theoretically, this study extends the application of Parsons' theory of frugality and social adaptation to the cultural context of Indonesian college students, by positioning frugal living as a moral practice and a form of counterculture to a consumptive lifestyle. Practically, the results of this study can serve as a basis for developing policies on financial literacy, character development, and student welfare based on socio-cultural values. The limitations of this study lie in the limited number of informants and research locations. Therefore, further research is recommended to expand the context and use a mixed methods approach to obtain more comprehensive results. Penelitian ini bertujuan untuk memahami strategi sosiobudaya yang digunakan oleh mahasiswa perguruan tinggi dalam menerapkan gaya hidup hemat di tengah tantangan ekonomi dan meningkatnya budaya konsumerisme di lingkungan pendidikan tinggi. Penelitian ini dilakukan di Universitas Negeri Semarang (UNNES) dengan menggunakan pendekatan deskriptif kualitatif. Data dikumpulkan melalui wawancara mendalam, observasi, dan dokumentasi yang melibatkan enam informan utama dan delapan informan pendukung yang dipilih secara purposif. Analisis data menggunakan model interaktif Miles dan Huberman, yang meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Temuan menunjukkan bahwa mahasiswa menerapkan tiga strategi utama: (1) pengelolaan keuangan rasional melalui perencanaan anggaran dan pemantauan pengeluaran; (2) pengendalian konsumsi dengan membatasi pengeluaran harian dan memprioritaskan kebutuhan dasar; dan (3) adaptasi sosiobudaya melalui internalisasi kesederhanaan, solidaritas sesama, dan nilai-nilai yang diwariskan keluarga. Strategi-strategi ini menunjukkan bahwa kesederhanaan bukan hanya respons ekonomi, tetapi juga ekspresi budaya yang membentuk identitas sosial mahasiswa. Secara teoritis, studi ini memperluas penerapan teori kesederhanaan dan kerangka kerja adaptasi sosial Parsons dalam konteks budaya mahasiswa Indonesia, menempatkan kesederhanaan sebagai praktik moral dan kontra-budaya terhadap konsumerisme. Secara praktis, hasil penelitian ini memberikan wawasan untuk mengembangkan program literasi keuangan, pendidikan karakter, dan kebijakan kesejahteraan mahasiswa yang berakar pada nilai-nilai sosial dan budaya. Penelitian ini dibatasi oleh jumlah informan yang sedikit dan cakupan institusional tunggal; oleh karena itu, penelitian masa depan sebaiknya memperluas konteksnya dan menggunakan metode campuran untuk mencapai pemahaman yang lebih komprehensif.